Molecular identification of Textile Azo Dye degrading bacterial strains by 16S rRNA sequencing and phylogenetic analysis - Momtareen, Taizina (BRAC University, 2017)
This Thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2016.